1977
DOI: 10.1002/1097-0142(197705)39:5<2204::aid-cncr2820390539>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Plasma ribonuclease.A marker for the detection of ovarian cancer

Abstract: There were no significant differences between the mean blood plasma (leu-kocyte-free) RNAuse activity among 128 healthy women volunteers age 13-70 and 49 women with benign gynecological tumors. Exceptions to this finding were three apparently healthy women volunteers who had plasma enzyme activity which was higher than two standard deviations from the mean of the control subjects. Increased plasma RNAase activity was also demonstrated for 21 of 22 patients with ovarian carcinomas of different histological type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

1980
1980
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Previous studies have documented the elevation of RNase activity in the circulation of cancer patients (9,10). Based on these observations, we hypothesized that plasma RNA integrity could be a potential marker for tumor detection and monitoring.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…Previous studies have documented the elevation of RNase activity in the circulation of cancer patients (9,10). Based on these observations, we hypothesized that plasma RNA integrity could be a potential marker for tumor detection and monitoring.…”
mentioning
confidence: 66%
“…High levels of RNases have previously been observed in the serum of pancreatic cancer patients (9) and in the plasma of ovarian cancer patients (10). The origin of such elevations, however, is still unknown.…”
Section: Discussionmentioning
confidence: 98%
“…There is evidence of elevated ribonuclease Probands and samples -activity due « faired renal function (245), during f-/ sp regnancy (6) and in catholic conditions (7). Some ^ ^ had ^ ^ mĂą uthors pointed out that the enzyme may be of vdue as ^ ^.^ ^ ^ < ^ ^Ăą cancer diagnostic (8,9,10). In recent publications Creatinine 1 ) < 100 /l; Creatinine-clearance > 100 ml/min this latter suggestion has been looked at more critically (13).…”
Section: Introductionmentioning
confidence: 99%
“…Several in vivo studies by our group revealed that administration of RNase1 in pathogenetic animal models had protective effects by, e.g., reducing thrombosis, preventing edema formation, or suppressing the pathological outcome of inflammation or tumor progression (7, 8, 11). Accordingly, RNase activity in sera of patients with different types of cancer (12, 13), pancreatic fibrosis (14, 15), or myocardial infarction (16) were changed in a disease‐related manner, indicating that the expression of vascular RNase1 appears to be responsive toward different pathological situations, possibly as a biomarker of disease progression or outcome.…”
mentioning
confidence: 99%